Wetland habitat disturbance best predicts metrics of an amphibian index of biotic integrity. (September 2015) - Stapanian, Martin A.; Micacchion, Mick; Adams, Jean V.
Graphical abstract: Highlights: We sought the best predictors of elements of an amphibian index of biotic integrity. Predictors included eight landscape- and five wetland-scale habitat variables. Best predictor for all elements was wetland-scale habitat condition and disturbance. This variable was also the best predictor of wetland vegetation integrity. Suggests similar management procedures for wetland vegetation and amphibians. Abstract: Regression and classification trees were used to identify the best predictors of the five component metrics of the Ohio Amphibian Index of Biotic Integrity (AmphIBI) in 54 wetlands in Ohio, USA. Of the 17 wetland- and surrounding landscape-scale variables considered, the best predictor for all AmphIBI metrics was habitat alteration and development within the wetland. The results were qualitatively similar to the best predictors for a wetland vegetation index of biotic integrity, suggesting that similar management practices (e.g., reducing or eliminating nutrient enrichment from agriculture, mowing, grazing, logging, and removing down woody debris) within the boundaries of the wetland can be applied to effectively increase the quality of wetland vegetation and amphibian communities.